Effects of nutrition on serum levels of thyroxine and triiodothyronine in reindeer (Rangifer tarandus tarandus) - Ryg, Morten; Jacobsen, Endre (Rangifer, 1981)
We have investigated effects of qualitative and quantitative differences in feed on serum concentrations on the thyorid hormones, thyroxine (T4) and triiodothyronine (T3). We have recorded hormone levels in groups of animals of different sex, age and weight. They were fed either a pelleted reindeer feed (RF 71, 13,7% protein) or lichen (3,4 protein), or a combination of RF 71 and lichen. 1. When going over from restricted to ad lib. feeding with the same kind of feed (RF 71), serum T3 increased, but nok T4. 2. Serum T3 or T4 did nok change when feed was changed from RF 71 to the same amount of dry matter of a combination of RF 71 and lichen. Neither were there any significant differences between a group fed RF 71 and a group fed a combination of RF 71 and lichen. 3. Serum T3 and dry matter intake were well correlated. We conclude that seasonal differences in T4 are partly independent of nutrition, while T3 was heavily influenced by nutrition, specifically the amount of dry matter consumed. Serum T3 can possibly be used to estimate dry matter intake. Ravitsemuksen vaikutus poron (Rangifer tarandus tarandus) seerumin tyroksiini ja trijodityroniinitasoon. Abstract in Finnish / Yhteenveto: Olemme tutkineet poron ravinnonsaannissa esiintyvien kvalitatiivisten ja kvantitathvisten erojen vaikutusta seerumin kilpirauhashormonien trijodityroniinin (T3) ja tyroksiinin (T4) konsentraatioon. Olemme rekisteroineet hormonipitoisuuksia iån, sukupuolen ja painon perusteella erilaisissa ryhmisså. Ruokinnassa on kåytetty pelletoitua poronrehua (RF 71, 13,7% proteiini ja/tai jåkålåå (3,4% proteiinia). 1. Siirryttåesså rajoitetusta rehunsaannista ad lib. ruokintaan samalla rehulla (RF 71), seerumin T3-taso kohosi, mutta ei T4-taso. 2. Siirryttåesså ruokinnassa RF 71-rehun kåytostå kuiva-ainepitoisuudeltaan vastaavan RF 71-rehun ja jåkålå-yhdistelmån kåyttoon ei havaittu merkitseviå muutoksia T3- tai T4-tasoisaa. Verrattaessa RF 71-rehua kåyttånyttå ryhmåå ja toista ryhmåå, jota ruokittiin rehun ha jåkålån yhdistelmållå ei myoskåån havaittu merkitseviå eroja. 3. Nautitun kuiva-ainemåårån ja seerumin T3-konsentraation vålillå vallitsee selvå korrelaatio. Me pååttelemme, ettå T4-tason vuodenaikaisvaihtelut ovat osittain riippumattomia ravitsemuksesta, kun taas ravinto selvåsti vaikuttaa T3-tasoon. Seerumin T3-arvoa voidaan ehkå kåyttåå poron nauttiman kuiva-ainemåårån arvioimiseen. Virkninger av ernæring på serumnivåer av thyroxin og triiodothyronin hos rein (Rangifer tarandus tarandus) Abstract in Norwegian / Sammendrag: Vi har undersøkt virkningen av kvalitative og kvantitative forskjeller i næringstilgang på konsentrasjonene av skjoldbruskkjertelhormonene triiodothyronin (T3) og thyroxin (T4) i serum hos rein. Vi har registrert hormonnivåer hos grupper av dyr med forskjellig alder, kjønn og vekt. De har vært foret med et pelletert reinfor (RF 71, 13,7% protein), og/eller lav (3,4% protein). 1. Ved overgang fra begrenset til ad lib. foring med samme for (RF 71) økte serum T3, men ikke T4. 2. Ved overgang fra RF 71 til samme tørrstoffmengde av en kombinasjon av RF 71 og lav, var det ikke signifikante endringer i T3 eller T4. Det var heller ikke signifikante forskjeller mellom en gruppe som ble foret med RF 71 og én som ble foret med RF 71 og lav. 3. Det var en god korrelasjon mellom tørrstoffinntak og serumkonsentrasjon av T3. Vi konkluderer med at årstidsvariasjonene i T4 delvis er uavhengige av ernæring, mens T3 er strengt ernæringsregulert. Serum T3 kan kanskje brukes til å estimere tørrstoffinntak hos rein.